Changing white attitudes toward Black political leadership - Hajnal, Zoltan (Cambridge University, 2013)
Despite the hopes of the civil rights movement, researchers have found that the election of African Americans to office has not greatly improved the well-being of the black community. By shifting the focus to the white community, this book finds that black representation can have a profound impact. Utilizing national public opinion surveys, data on voting patterns in large American cities, and in-depth studies of Los Angeles and Chicago, Zoltan Hajnal demonstrates that under most black mayors there is real, positive change in the white vote and in the racial attitudes of white residents. This change occurs because black incumbency provides concrete information that disproves the fears and expectations of many white residents. These findings not only highlight the importance of black representation; they also demonstrate the critical role that information can play in racial politics to the point where black representation can profoundly alter white views and white votes.